A Relevance Theory Approach to the Pragmatic Interpretation of Surah Al-Mulk Pendekatan Teori Relevan terhadap Interpretasi Pragmatik Surah al-Mulk - Mohd Ismath, Nurul Hanilah; Abd Aziz, Abdul Hadi (QURANICA - International Journal of Quranic Research, 2025)
The Qur’ān employs a wide range of rhetorical strategies in conveying its message to humanity, referred to in Arabic as uslūb (plural: asālīb). Among these strategies is the use of interrogative constructions. A considerable number of interrogative verses in the Qur’ān are not intended to function as literal questions; rather, they convey layered and implicit meanings. Inaccurate interpretation of such interrogatives may therefore lead to a distorted understanding of the Qur’ānic message. This study aims to identify interrogative verses in Sūrah al-Mulk and to elucidate both their explicit and implicit meanings within their respective textual contexts. Data analysis is conducted through a pragmatic framework grounded in Relevance Theory as proposed by Sperber and Wilson (1986), adapted to Qur’ānic textual analysis through reference to authoritative classical exegetical works (tafsīr muʿtabar). A total of twelve interrogative verses were identified in Sūrah al-Mulk and selected as the corpus of analysis. The findings reveal that interrogative constructions in Sūrah al-Mulk serve a range of rhetorical functions, including admonition, warning, threat, reproach, and the evocation of fear in the audience. Such usage underscores the aesthetic refinement, semantic depth, and expressive richness of Qur’ānic discourse in guiding human reflection and moral awareness. Accordingly, the ability to discern both the explicit and implicit meanings of Qur’ānic interrogatives is essential for Muslims, in order to avoid misinterpretation of the divine message.